Educational Program with Text Messaging for Community-Dwelling Patients with Hypertension: A Pilot Randomized Controlled Trial - Hon Lon Tam; Eliza Mi Ling Wong; Kin Cheung (Asian Nursing Research, 2023)
Summary: Purpose: Controlling blood pressure minimizes the risk of cardiovascular events among patients with hypertension. Despite regular follow-ups, the hypertension management for patients aged ≥45 years is limited as evidenced from a decreased control rate. This pilot study aimed to test a theory-guided educational program for community-dwelling patients with hypertension. Methods: Sixty-nine patients with hypertension aged ≥45 years and having high blood pressure (>130/80 mmHg) were recruited in this two-arm pilot randomized controlled trial. Participants in the intervention group underwent a program guided by the Health Promotion Model, whereas those in the control group received usual care. Data were collected at baseline, week 8, and week 12 and used to assess the blood pressure, pulse pressure, self-efficacy, and adherence to hypertension management. Data were analyzed using a generalized estimating equation based on the intention-to-treat principle. Process evaluation was conducted to assess the feasibility and acceptability of the educational program. Results: The results obtained using the generalized estimating equation revealed that the educational program led to reduction in the systolic blood pressure (β = −7.12, p = .086) and pulse pressure (β = −8.20, p = .007) and to improve self-efficacy (β = 2.61, p = .269) at week 12. The program had a small-to-moderate effect on the reduction of systolic blood pressure (effect size = −0.45) and pulse pressure (effect size = −0.66) and self-efficacy (effect size = 0.23). The participants were highly satisfied with the educational program. Conclusions: The educational program was found to be feasible and acceptable and may be incorporated into current hypertension management practices at the community level. Trial registration: ClinicalTrials.gov with identifier: NCT04565548.